Manajemen Identitas dalam Komunikasi Antarbudaya antara Freelancer dan Klien di Platform Fiverr (Studi Kasus Agensi Lummyseen) - Paujiatul Arifah; Naila Sabrina Zalfa (Asosiasi Dosen Muda Indonesia, 2025)
Digital transformation and the growth of the gig economy have significantly reshaped professional work patterns, particularly for freelancers who engage with culturally diverse clients through digital platforms such as Fiverr. In this context, technical skills alone are insufficient; freelancers are also required to strategically manage communication and professional identity. This study aims to analyze intercultural communication dynamics and professional identity management strategies employed by freelancers at Lummyseen Agency in their interactions with clients on the Fiverr platform. This research adopts a qualitative approach using Edmund Husserl’s phenomenological method. Data were collected through in-depth interviews, observation, documentation, and literature review, with informants selected through purposive sampling from active freelancers at Lummyseen Agency. Data analysis focused on exploring freelancers’ subjective experiences in constructing, presenting, and negotiating their professional identities. The findings reveal that professional identity management is conducted consciously and strategically through the management of communication competence, self-identity, cultural identity, and facework practices in digital interactions. Freelancers adapt their communication styles, regulate emotions, and apply netiquette to address challenges related to language barriers, cultural differences, and stereotypes. This study concludes that professional identity management is a dynamic and ongoing process that plays a crucial role in building credibility, trust, and sustainable intercultural working relationships within the platform-based gig economy.